Atlas of European millipedes 2: Order Julida (Class Diplopoda) - Kime, Richard Desmond; Enghoff, Henrik (European Journal of Taxonomy, 2017)
For each of the 593 species of the millipede order Julida known from Europe, available information on taxonomy, distribution and habitat is summarized, and the distribution in 50 × 50 km UTM squares is shown on a map.